Deoxyribonuclease Is a Potential Counter Regulator of Aberrant Neutrophil Extracellular Traps Formation after Major Trauma. (23rd January 2012) - Meng, Wei; Paunel-Görgülü, Adnana; Flohé, Sascha; Witte, Ingo; Schädel-Höpfner, Michael; Windolf, Joachim; Lögters, Tim Tobias
Abstract : Introduction . Neutrophil extracellular traps (NET) consist of a DNA scaffold that can be destroyed by Deoxyribonuclease (DNase). Thus DNases are potential prerequisites for natural counter regulation of NETs formation. In the present study, we determined the relationship of NETs and DNase after major trauma. Methods . Thirty-nine major trauma patients, 14 with and 25 without sepsis development were enrolled in this prospective study. Levels of cell-free (cf)-DNA/NETs and DNase were quantified daily from admission until day 9 after admission. Results . Levels of cf-DNA/NETs in patients who developed sepsis were significantly increased after trauma. In the early septic phase, DNase values in septic patients were significantly increased compared to patients without sepsis (P < 0.05 ). cf-DNA/NETs values correlated to values of DNase in all trauma patients and patients with uneventful recovery (P < 0.01 ) but not in septic patients. Recombinant DNase efficiently degraded NETs released by stimulated neutrophils in a concentration-dependent manner in vitro. Conclusions . DNase degrades NETs in a concentration-dependent manner and therefore could have a potential regulatory effect on NET formation in neutrophils. This may inhibit the antibacterial effects of NETs or protect the tissue from autodestruction in inadequate NETs release in septic patients.